Universitas Trunojoyo Madura - Aena Wati; Siti Nur Aisyah; Ahmad Budi Utomo (Universitas Trunojoyo Madura, 2017)
The effort to develop this batik kampong tourism is with the new innovation which aims to increase the attraction of outsiders to visit, recognize and consume typical batik Tanjung Bumi district. These innovations include the existence of Griya Adat Nusantara. Kampung batik nuanced nuance griya nusantara as a container to develop and optimize the potential of batik in the area. So the economy of Tanjung Bumi people can increase. The program has authority in the management of intangible local assets through batik culture. From the above description, supported by the Law no. 6 Year 2014 is about the Village which one of the goals is to encourage the initiative, movement, and participation of the village community for the development of potential and Village Assets for the common welfare. Writing methods used in this paper is descriptive qualitative in order to obtain a real picture of the problem and provide a solution. In addition, this paper uses a SWOT analysis strategy to evaluate Strength, Weakness, Opportunities and Threats in the presentation of the proposed program. The type of data used is secondary data as a reference. This program is the latest innovation to develop the potential of the village from the left into an independent village and prosperous, in addition to improving the economy, the existence of batik kampong tourism as well as educative and batik learning facilities. The high level of program realization and support from Local Government, Village Government and Batik Craftsmen in Tanjung Bumi will assist in realizing this program